Electron-Beam Welding Cu and Al6082T6 Aluminum Alloys with Circular Beam Oscillations - Darina Kaisheva; Angel Anchev; Vladimir Dunchev; Georgi Kotlarski; Borislav Stoyanov; Maria Ormanova; Stefan Valkov (Crystals, 2022)
In this study, we present the results from electron-beam welding operations applied on copper and Al6082T6 aluminum alloys. The influence of beam-scanning geometries on the structure and mechanical properties of the welded joint is studied. The experiments were conducted using a circle oscillation mode with an oscillation radius of 0.1 mm and 0.2 mm. The beam deflection was set to 0.4 mm with respect to the side of the aluminum alloy, and the beam power was set at 2700 W. The phase composition of the obtained welded joints was studied by X-ray diffraction (XRD). Scanning electron microscopy (SEM) was used for the investigation of the microstructure of the joints. The chemical composition was investigated by using energy-dispersive X-ray spectroscopy (EDX). The mechanical properties were studied by micro-hardness investigations. The fusion zone of the weld seam contains three phases—an aluminum matrix, an ordered solid solution of copper and aluminum in the form of CuAl2, and pure copper. Electron beam-scanning geometries have significant influences on the structure of the weld. Increasing the beam oscillation’s radius leads to a decrease in intermetallic phases and improves homogeneity. The measured microhardness values in the fusion zone are much higher than the ones measured in the base metals due to the formation of intermetallic phases. The microhardness of the weld joint formed using an oscillation radius of 0.2 mm was much lower compared to the one formed using an oscillation radius of 0.1 mm.